Sensitivity of Maximum Current Protection in the case of 6-10 kV Air Power Line Back - G. F. Kutsenko; A. A. Parfenov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2003)
The paper contains results of the investigations that reveal the possibility of mutual back-up of 6-lOkV air power lines in the case of emergency power supply switching of any line on condition that operation of the current protection system is initiated. The air power lines of the Gomel power networks have been taken as an example for the execution of the investigations